Propertization: The process by which financial corporate power has risen and collapsed - Jongchul Kim (Review of Capital as Power, 2018)
Elsewhere I argue that the legal concept of property was created in the image of money in the late Roman Republic. Since then, the division of property and contract has been an underlying structure of Western law. The paper argues that a main way of structuring financial corporate power, especially money market funds (MMFs), is a propertization of contractual claims. Propertization here means to grant property rights to shareholders who are almost reduced to functionless debenture holders and thus supposed to have only contractual claims. The paper argues that this propertization has led to the rise of financial corporate power, especially MMFs and their money-creation mechanism. The paper also explores how the propertization of MMF shares contributed to generating the financial crisis of 2008, and it ends by briefly discussing a possible MMF reform policy.
Keywords: 330; Property; propertization; finance; corporate power; money market funds; financial crisis; money; credit; contract; shares; repurchase agreem